Yeast Three-Hybrid Screening of Rous Sarcoma Virus Mutants with Randomly Mutagenized Minimal Packaging Signals Reveals Regions Important for Gag Interactions - Lee, Eun-Gyung (American Society for Microbiology, 2000)
We previously showed that the yeast three-hybrid system provides a genetic assay of both RNA and protein components for avian retroviral RNA encapsidation. In the current study, we used this assay to precisely define cis-acting determinants involved in avian leukosis sarcoma virus packaging RNA binding to Gag protein. In vivo screening of Rous sarcoma virus mutants was performed with randomly mutated minimal packaging sequences (MΨ) made using PCR amplification after cotransformation with GagΔPR protein into yeast cells. Colonies with low β-galactosidase activity were analyzed to locate mutations in MΨ sequences affecting binding to Gag proteins. This genetic assay delineated secondary structural elements that are important for efficient RNA binding, including a single-stranded small bulge containing the initiation codon for uORF3, as well as adjacent stem structures. This implies a possible tertiary structure favoring the high-affinity binding sites for Gag. In most cases, results from the three-hybrid assay were well correlated with those from the viral RNA packaging assays. The results from random mutagenesis using the rapid three-hybrid binding assay are consistent with those from site-directed mutagenesis using in vivo packaging assays.